Comparison of the physicochemical properties of palm-based shortenings of various melting temperatures and animal fats - Faridah, Mohd Razali; Hairi, Amelia Najwa Ahmad; Mat Yusoff, Masni; Rozzamri, Ashari; Wan Ibadullah, Wan Zunairah; Ismail-Fitry, Mohammad Rashedi (Elsevier, 2025)
This study compares the physicochemical properties of palm-based shortenings (PS) with varying melting temperatures (33–60 °C) to animal fats from chicken, beef, and mutton. Key parameters assessed include peroxide value, solid fat content, thermal behaviour, fatty acid composition, and crystal structure. PS exhibits lower peroxide values (0.45–8.33 meq/kg) than animal fats (5.02–12.21 meq/kg), indicating greater oxidative stability. PS with higher melting points (55–60 °C) demonstrates enhanced solid fat content (up to 98 % at 10 °C) and thermal stability, while lower-melting PS (33–42 °C) displays β’ crystal dominance, closely resembling the texture of animal fats. Principal component analysis reveals that chicken fat clusters with PS of 33–49 °C, suggesting that these PS can directly substitute animal fats in food applications. Palm-based shortenings with melting points ranging from 33 to 49 °C exhibit functional and structural characteristics that position them as effective and sustainable alternatives to animal fats (particularly chicken fat).